2019
DOI: 10.1136/bmjopen-2019-031969
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia prevalence and associated risk factors in the United Arab Emirates: a population-based study

Abstract: ObjectivesTo determine and describe the prevalence and pattern of dyslipidaemia and its associated risk factors among an adult Emirati population.DesignPopulation-based, cross-sectional study.SettingAdults living in the Northern Emirates.Participants824 adult participants (51.8% men, 48.2% women, mean age 42.8±13.4 years old).Primary outcome measuresFasting blood samples were collected, blood pressure and waist circumference were measured.ResultsThe overall dyslipidaemia prevalence was 72.5%, with 42.8% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 29 publications
2
31
3
4
Order By: Relevance
“…For instance, research suggests that vigorously contracting muscle can release large quantities of myokines with auto-, para-, and endocrine effects. The best-studied myokine is Interleukin-6 (IL-6) which, among a myriad of functions, stimulates β -cell proliferation, reduces stress induced β -cell apoptosis, and increases glucose transporter (GLUT4) translocation, thus, basal glucose uptake [ 36 ]. Moreover, the well-documented benefits of physical activity supersede molecular adaptations of working skeletal muscle and include improvement of coronary endothelial function, enhancement of muscle strength and power, and reduction in the aging process or sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, research suggests that vigorously contracting muscle can release large quantities of myokines with auto-, para-, and endocrine effects. The best-studied myokine is Interleukin-6 (IL-6) which, among a myriad of functions, stimulates β -cell proliferation, reduces stress induced β -cell apoptosis, and increases glucose transporter (GLUT4) translocation, thus, basal glucose uptake [ 36 ]. Moreover, the well-documented benefits of physical activity supersede molecular adaptations of working skeletal muscle and include improvement of coronary endothelial function, enhancement of muscle strength and power, and reduction in the aging process or sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a strong association between WC (a surrogate marker of visceral adiposity), FPG, elevated DBP, and multiple dyslipidemias persisted in the multivariable logistic regression analysis. These associations have been observed in younger cohorts [25,36]. From a more practical perspective, computed tomography (CT) studies have demonstrated that visceral adiposity is more closely related to lipid, glucose, and blood pressure abnormalities [37].…”
mentioning
confidence: 98%
“…However, comparable results have been reported by some investigators in the region. A study conducted in Nigeria reported a frequency of 85.9% 6 , 67.3% in South Africa 19 , United Arab Emirates 72.5% 21 , Makelle city, Northern Ethiopia (66.7%) 22 , India (ICMR-INDIAB study) (79%) 23 , Northern China (31.2%) 24 , and USA (52%) 25 . Separately, some estimates of the prevalence of dyslipidemia among adults in Africa place the value between 15% to about 50% 4,26 .…”
Section: Discussionmentioning
confidence: 99%
“…In the United Arab Emirates (UAE), ischemic heart diseases and stroke are among the top 3 leading causes of years of life lost (YLL) and mortality according to a global burden disease study in 2016 (3). Another recent study in UAE showed that the overall prevalence of dyslipidemia among adults was 72.5%, where the total cholesterol and LDL-C levels were high in 42.8% and 38.6% of the participants, respectively (4). In addition, a study including an expatriate population in the UAE reported a high prevalence of either overweight or obesity (75.3%) as well as known associated risk factors for developing both metabolic syndrome and dyslipidemia (5).…”
Section: Introductionmentioning
confidence: 99%